Free Library Data? - Bérard, Raymond (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2011)
As library materials are catalogued by public organisations and librarians are active promoters of the principles of open access, one would expect library data to be freely available to all. Yet this is not the case. Why then do so few libraries make their data available free of charge? This article reviews the diverging, often restrictive policies and the interests (commercial and strategic) at stake. It presents a panorama of the current situation, the actors and interests involved. It addresses the legal aspects and the obstacles and it shows how data produced by libraries can be made freely available to other knowledge organisations while retaining and developing the collective organisations and services built by library networks over the years. The aim of the ‘free the data movement’ is to share and reuse bibliographic data in a new ecosystem where all the actors are involved, both users and providers, not just librarians.